PEMBELAJARAN BAHASA ARAB DARING (Studi Kasus Mahasiswa Hukum Kelurga Islam (HKI) STAI Taruna Surabaya) - Saiul Ana (Program Studi Pendidikan Bahasa Arab Unisda Lamongan, 2020)
The Covid 19 emergency outbreak was imposed by the Indonesian government, and the minister of education launched a study from home since March 2020. Learning is done online / in accordance with government regulations to break the spread of the epidemic. In general, low-grade Institute student still have problems recognizing Arabic letters. This will cause students difficulty learning Arabic subjects. This study describes the teaching of Arabic for HKI students , with research subjects HKI students In STAI Taruna Surabaya, totaling 11 students, and Arabic language lecturing. Data collection methods used observation and interviews to determine the teaching methods used, and the constraints faced by lecture and students. The results showed that online Arabic teaching for student used the lecture method. The obstacles faced by lectures are the lack of opportunities to monitor one by one student and many students who cannot attend while the obstacle for students is the lack of understanding of the lessons conveyed by the lecture, internet network connections that do not support.